1992
DOI: 10.1111/j.1348-0421.1992.tb01667.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Flagella of Vibrios: Serological Classification and Genetical Similarity

Abstract: Lateral (L-) flagella-having vibrios were classified into 13 H-serogroups (flagellar antigen serogroups) by means of H-agglutination test. Vibrio parahaemolyticus was classified into 3 serogroups, HL1 to 3. V. alginolyticus and V. harveyi were classified into 5 and 3 serogroups, respectively, but 2 of those were serogroups common to the both species. V. fluvialis and V. furnissii constituted a same serogroup, HL8. Cross-reactivity between each serogroup was not observed in H-agglutination test, although some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…It is a primary cause of seafood‐associated food poisoning worldwide. Lateral flagella have also been described on about seven other Vibrio species (some of which have a similar disease spectrum to V. parahaemolyticus ) [4], as well as only a small number of other bacterial species. These species are Rhodospirillum centenum (a purple photosynthetic bacterium) [5], Azospirillum spp.…”
Section: Bacterial Species With Two Distinct Flagellar Systemsmentioning
confidence: 99%
“…It is a primary cause of seafood‐associated food poisoning worldwide. Lateral flagella have also been described on about seven other Vibrio species (some of which have a similar disease spectrum to V. parahaemolyticus ) [4], as well as only a small number of other bacterial species. These species are Rhodospirillum centenum (a purple photosynthetic bacterium) [5], Azospirillum spp.…”
Section: Bacterial Species With Two Distinct Flagellar Systemsmentioning
confidence: 99%
“…Tassin et al (1983) and Shinoda et al (1984) demonstrated independently that anti- L -flagella antisera of V. fluvialis did not agglutinate other Vibrio species in the H-agglutination tests. Further studies placed V. fluvialis and V. furnissii in the same lateral flagellar serogroup-HL8 (Shinoda et al, 1992). However, in practice, serotyping based on H-flagella is also not in use.…”
Section: Phenotypic and Genetic Characteristics Of V Fluvialismentioning
confidence: 95%
“…In addition, the V. campbellii genome encodes genes that are homologous to V. parahaemolyticus lateral flagellar genes for swarming motility. However, only a few strains express these genes with little phenotypic or genetic characterization (Allen & Baumann, 1971;Shinoda et al, 1992). It has been shown that the regulatory hierarchy of V. campbellii transcription of the flagellar and chemotaxis genes is similar to that of other Vibrio spp.…”
Section: Vibrio Sppmentioning
confidence: 99%